Biokinetics and Estimation of Dose from 99mTc-Labelled Polyclonal Human Immunoglobulin (HIG) - Saptogino, A.; Becker, W.; Wolf, F. (Nuklearmedizin - NuclearMedicine, 1991)
Recently, polyclonal unspecific human immunoglobulin was suggested as a new agent for the localization of inflammatory lesions. Little information about the biodistribution of this radiopharmaceutical was reported so far. To obtain further information, 99mTc-labelled human immunoglobulin (HIG) was administered to a volunteer with presumed normal biokinetics. The absorbed doses to the organs were calculated according to the MIRD concept. The scintigraphic images at 1, 2, 4 and 24 h post injection demonstrated a prolonged activity retention in the blood and high activity in the kidneys, bladder and also in the liver. No significant uptake in the bowels and the marrow could be observed over the whole period of study. 27.4% of the administered activity was excreted in the urine within 24 h. The calculated organ absorbed doses, all in μGy/MBq, were estimated as follows: whole body 2.7, liver 7.3, spleen 12.0, kidneys 15.3, lungs 3.2, marrow 9.6 and gonads 17.0. From these results an effective dose equivalent of 7.9 • 10−3 mSv/MBq was calculated. The cancer risk estimate of 5 • 10−5, using 370 MBq 99mTc-HIG, may be considered quite low in comparison to other scintigraphic methods of diagnosing inflammation.Über die Biodistribution von 99mTc- markiertem humanem Immunglobulin, einem neuen Pharmakon zur Lokalisation entzündlicher Erkrankungen, liegen bislang am Menschen nur unzureichende Daten vor. Bei einem freiwilligen Probanden, bei dem eine physiologische Biokinetik vorausgesetzt werden konnte, wurden diese Daten erhoben und die Organdosen gemäß dem MIRD-Konzept berechnet. Planare Szintigramme in p.a.- und a.p.-Projektion nach 1, 2, 4 und 24 h p.i. ließen eine prolongierte Aktivitätsretention im Blut und einen Nieren-, Blasen- und Leber-Uptake erkennen. Ein signifikanter Darmoder Knochenmarksuptake war während der gesamten Untersuchungsdauer nicht zu registrieren. 27,4% der applizierten Aktivität wurden renal eliminiert. Die Organdosen (in μGy/ MBq) wurden wie folgt abgeschätzt: Ganzkörper 2,7; Leber 7,3; Milz 12,0; Nieren 15,3; Lungen 3,2; Knochenmark 9,6; Gonaden 17,0. Aus diesen Ergebnissen wurde ein effektives Dosisäquivalent von 7,9 × 10−3 mSv/MBq errechnet. Das Ergebnis der Krebsrisikoabschätzung von 5 × 10−5 beim Einsatz von 370 MBq 99mTc-HIG erwies sich im Vergleich zu anderen szintigraphischen Techniken zur Entzündungslokalisation als recht niedrig.